Municipal property asset management – a comparative study of UK and Russia - Phelps, Alan (International Journal of Strategic Property Management, 2012)
Property asset management is a discipline of growing significance for local government across the world. The perceived wisdom of transition countries lagging behind developed countries in the maturity of asset managent has not been tested with empirical data. An analytical framework was developed comprising models to measure why councils do asset management (rationale); how they do it (practice) and what they achieve (outcomes) and applied through a comparative study of municipalities in the UK and Russia. A weak but discernable link was found between rationale and practice but the link between practice and outcomes was unproven. Russia appeared to lag UK in its development of asset management and case studies in both countries had a consistent view of the critical success factors for effective asset management. These were strategic focus, organisation will, portfolio intelligence and an entrepreneurial culture. The research used the strength of these factors with the analysis of rational, practice and outcomes to position cases in a typology which provided a simple metric to position organisations in terms of both their maturity and development path in asset management.First Publish Online: 11 Jan 2012